The reduction of novice drivers' accidents requires improved perception and reduced acceptance of risk - Gerald J.S. Wilde (Université de Provence, 2013)
We know that beginner drivers are overrepresented in national road accident statistics. Drivers under age 25 commonly account for about twice as many accidents as their proportion in the total driver population, while their accident involvement diminishes with every additional year of driving. We know, too, that about one-half of the overrepresentation of novice drivers in the accident statistics is due to inexperience, and the other half to characteristics associated with being young. Lack of experience implies a lower level of driving skills; we will argue here that this is largely due to (a) a salient deficiency in the ability of beginner drivers to recognize risk as more experienced drivers do, and (b) overconfidence in their ability to handle the challenges to their safety; and not to their limited vehicle-handling skills. We therefore, first describe a teaching technique to help accelerate the acquisition of risk-perception skills by novice drivers. Secondly, we argue that the age-related overrepresentation of young drivers in the accident statistics is due to a higher-than-average level of willingness to take risks. We discuss the major determinants of risk acceptance and present incentives for accident-free performance as the most effective method for bringing down the accepted level of risk while driving, and thus the frequency of accidents.